Die Kunst der Theatereröffnung. Ästhetik und Kulturpoetik von Vorreden und Vorspielen vom 17. Jahrhundert bis heute [in Vorbereitung] (Marta Famula ist Herausgeberin der Schriftenreihe "Drama zwischen Text und Bühne" zus. mit Agata Mirecka und Paul Martin Langner)

Exploring the importance of prior knowledge and verbal cognitive abilities for foreign language learning - Rumlich, Dominik (Cognition and second language acquisition)

Attitudes of German high school students toward different varieties of English - Meer, Philipp; Hartmann, Johanna; Rumlich, Dominik (Applied Linguistics)

Theater und Krise. Paradigmen der Störung in Dramentexten und Bühnenkonzepten nach 2000 (Marta Famula ist Herausgeberin der Schriftenreihe "Drama zwischen Text und Bühne" zus. mit Agata Mirecka und Paul Martin Langner)

Weniger Kompetenz, mehr Resonanz. Contra Position - Rumlich, Dominik (Fremdsprachen Lehren und Lernen)

Software-gestützte Planung der Smart-Service-Transformation - Reinhold, Jannik; Siewert, Michael; Scholtysik, Michel; Rasor, Anja; Koldewey, Christian; Dumitrescu, Roman (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Smart Services eröffnen vielfältige Geschäftsmöglichkeiten für produzierende Unternehmen und erfordern zugleich einschneidende Anpassungen ihrer häufig historisch gewachsenen Wertschöpfung. Dieser Beitrag zeigt eine Web-Applikation, die es produzierenden Unternehmen erlaubt, die erforderliche Smart-Service-Transformation zu planen. Dafür werden umfassendes Lösungswissen bereitgestellt und eine individuelle Gestaltungsempfehlungen für die zukünftige Wertschöpfung als Smart-Service-Anbieter gegeben.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Characterization of Usage Data with the Help of Data Classifications - Panzner, Melina; von Enzberg, Sebastian; Meyer, Maurice; Dumitrescu, Roman (Journal of the Knowledge Economy)
Abstract Comprehensive data understanding is a key success driver for data analytics projects. Knowing the characteristics of the data helps a lot in selecting the appropriate data analysis techniques. Especially in data-driven product planning, knowledge about the data is a necessary prerequisite because data of the use phase is very heterogeneous. However, companies often do not have the necessary know-how or time to build up solid data understanding in connection with data analysis. In this paper, we develop a methodology to organize and categorize and thus understand use phase data in a way that makes it accessible to general data analytics workflows, following a design science research approach. We first present a knowledge base that lists typical use phase data from a product planning view. Second, we develop a taxonomy based on standard literature and real data objects, which covers the diversity of the data considered. The taxonomy provides 8 dimensions that support classification of use phase data and allows to capture data characteristics from a data analytics view. Finally, we combine both views by clustering the objects of the knowledge base according to the taxonomy. Each of the resulting clusters covers a typical combination of analytics relevant characteristics occurring in practice. By abstracting from the diversity of use phase data into artifacts with manageable complexity, our approach provides guidance to choose appropriate data analysis and AI techniques.
Keywords: Economics and Econometrics

Business-to-Analytics Canvas - Translation of Product Planning-Related Business Use Cases into Concrete Data Analytics Tasks - Panzner, Melina; Meyer, Maurice; Enzberg, Sebastian von; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Value Creation Framework and Roles for Smart Services - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

To Fix or Not to Fix: A Critical Study of Crypto-misuses in the Wild - Wickert, Anna-Katharina; Baumgärtner, Lars; Schlichtig, Michael; Mezini, Mira
Recent studies have revealed that 87 % to 96 % of the Android apps using cryptographic APIs have a misuse which may cause security vulnerabilities. As previous studies did not conduct a qualitative examination of the validity and severity of the findings, our objective was to understand the findings in more depth. We analyzed a set of 936 open-source Java applications for cryptographic misuses. Our study reveals that 88.10 % of the analyzed applications fail to use cryptographic APIs securely. Through our manual analysis of a random sample, we gained new insights into effective false positives. For example, every fourth misuse of the frequently misused JCA class MessageDigest is an effective false positive due to its occurrence in a non-security context. As we wanted to gain deeper insights into the security implications of these misuses, we created an extensive vulnerability model for cryptographic API misuses. Our model includes previously undiscussed attacks in the context of cryptographic APIs such as DoS attacks. This model reveals that nearly half of the misuses are of high severity, e.g., hard-coded credentials and potential Man-in-the-Middle attacks.

Facharbeiten schreiben - Informationen für Schülerinnen und Schüler - Scharlau, Ingrid; Schreiber, Christine (Psychologieunterricht)

2022 Edsger W. Dijkstra Prize in Distributed Computing - Aguiliera, Marcos; Richa, Andréa W.; Schwarzmann, Alexander A.; Panconesi, Alessandro; Scheideler, Christian; Woelfel, Philipp (PODC ’22: ACM Symposium on Principles of Distributed Computing, Salerno, Italy, July 25 - 29, 2022)

A Thermal Model for Recuperative Heat Engines Operating with Dense Working Fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Inguva, Venkatesh; Kenig, Eugeny Y. (1st Conference on Energy, Environment and Digital Transition E2DT)

36th International Symposium on Distributed Computing, DISC 2022, October 25-27, 2022, Augusta, Georgia, USA

Reactive Direct Bonding of Digital Light Process Components - Moritzer, Elmar; Driediger, Christine (Macromolecular Symposia)
Keywords: digital light processing; material combination; reactive direct bonding; vat photopolymerization

Mit Gestaltungsrichtlinien zum Erfolg - Moritzer, Elmar; Elsner, Christian Lennart (Kunststoffe)

Why do Digital Platforms succeed or fail? - A Literature Review on Success and Failure Factors - Özcan, Leon; Koldewey, Christian; Duparc, Estelle; van der Valk, Hendrik; Otto, Boris; Dumitrescu, Roman
In the course of digitalization, digital platforms are unleashing their full disruptive potential and are already dominating the first industries (e.g., hotel industry). As a result of this success, more and more companies want to build their own platforms and participate in the success. However, building and operating a digital platform involves multiple challenges and most of such ambitions fail. Since most digital platforms fail, strategic leadership of digital platforms must consider both success factors and reasons for platform failure. For this purpose, we conducted a systematic literature analysis and identified 24 success as well as failure factors in 9 dimensions. From a scientific perspective, the article provides a structured analysis of success and failure factors of digital platforms, which previously did not exist in literature. Practitioners can use the resulting knowledge base to successfully manage platform activities and avoid pitfalls.
Keywords: Digital Platform; Multi-sided Market; Two-sided Market; Success Factor; Failure Factor

Task Mapping for Hardware-Accelerated Robotics Applications using ReconROS - Lienen, Christian; Platzner, Marco

Hundertstelmillimeter - Scharlau, Ingrid (Reflexive Schreibwissenschaft)

Corrosion Phenomena and Fatigue Behavior of Clinched Joints: Numerical and Experimental Investigations - Harzheim, Sven; Ewenz, Lars; Zimmermann, Martina; Wallmersperger, Thomas (Journal of Advanced Joining Processes)
Lightweight construction has increasingly become the focus of scientific research in recent years, not least due to the constantly increasing fuel price, which is a key factor in the economic viability of many companies. In this respect, the use of hybrid structures, made of dissimilar materials offers many advantages. However, such hybrid structures often have undesirable side effects. For example, brittle intermetallic phases are formed when aluminum and steel are welded. Clinching as a mechanical joining process does not produce such intermetallic phases since the connection is realized through form and force closure. In this process, a punch passes through two or more sheets and forms them into a permanent joint in a die. In the present work, the corrosion phenomena of an aluminum-steel clinched joint have been investigated by both experiments and numerical simulations in order to explain the superior fatigue behavior of pre-corroded joints. Therefore, the clinched joints have been corroded by a three-week salt-spray test. In addition, the electric potential and the von Mises stress are calculated under the assumption of a static loading. The results of both experiments and numerical simulations can explain the improvement in the fatigue behavior of the corroded specimens. This phenomenon can be attributed to the accumulation of corrosion products in small gaps between the joined metal sheets.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)